Comparison of Ketamine-Propofol and Fentanyl-Propofol on Intraoperative Hemodynamic Stability in Endoscopic Procedures - Ghazi Safadi, Ellen; Gasmalla Mohamed Ibrahim, Ghazi; Shaji, Ashli; Kumar Kandakurti, Praveen; Musa Abdalla Elamin, Sara (Journal of Neonatal Surgery, 2025)
Background: Deep sedation is commonly used for endoscopic procedures and is often achieved with combinations of anesthetic agents. Aims: This study compares ketamine-propofol (Ketofol) versus fentanyl-propofol (Fentofol) for maintaining intraoperative hemodynamic stability during endoscopy. Settings and Design: The study is a prospective observational comparison conducted at Thumbay University Hospital, Ajman, UAE. Methods and Materials: A prospective observational comparison was conducted in 100 adult patients (50 per group) undergoing various endoscopic procedures under deep sedation at a single centre. Systolic blood pressure, diastolic blood pressure, mean arterial pressure, and heart rate were recorded at baseline and 3-minute intervals intraoperatively. Results: Both sedation regimens provided adequate anesthesia without serious adverse events. Early intraoperative hemodynamic readings were similar between groups (p > 0.05). However, at certain time points during the procedure (around 6 and 15 minutes after induction), the ketamine-propofol group exhibited significantly higher blood pressure readings (closer to baseline) compared to the fentanyl-propofol group (p < 0.05), indicating more stable hemodynamics. Heart rate did not differ significantly between the two combinations at any time. Conclusion: Ketamine-propofol deep sedation maintained intraoperative hemodynamic stability more effectively than fentanyl-propofol in endoscopic procedures, particularly in preventing blood pressure drops during the procedure. These findings support the preferential use of ketamine-propofol for sedation in high-risk endoscopic cases where maintaining blood pressure is crucial.